The Use of Dall-E Artificial Intelligence Platform for Enhancing Students’ Vocabulary Acquisition - Fannoni, Bhimbi Imam; Priyana, Joko; Hidayatulloh, Sibakhul Milad Malik; Adhani, Ratisa (VELES Voices of English Language Education Society, 2023)
The use of technology in the field of English Language Teaching (ELT) has been valued giving positive results proven by scholars. However, among myriad research on the use of technology, little has been discussing the influence of AI in expanding students’ vocabulary acquisition. In contrast, previous researchers were limited to examining the effect of web-based 2.0 on several micro and macro skills. In fact, the use of Artificial Intelligence (AI) web-based platforms seems promising because of its innovation. Therefore, this paper aims at examining the effectiveness of the DALL-E AI platform in increasing the students’ vocabulary acquisition. To reach the aim, experimental design was employed. This current research invited thirty-one senior high school students from one of Islamic based schools in Yogyakarta. Three treatments were conducted along with a pretest before the treatments and posttest after the treatments. A paired-sample t-test showed an increasing score mean from 56.35 in the pretest to 67.58 in the posttest. Apart from the mean results, the t-test revealed that there was a significant difference between the pretest and posttest mean, where the significance value was at .000. By finding this, the alternative hypothesis is accepted. In accordance with the result, it could be asserted that the DALL-E Platform could be employed by the teacher to expand the students’ vocabulary acquisition.